Workfare and food in remote Australia: 'I haven't eaten… I'm really at the end…'. Issue 1 (1st February 2022) - Staines, Zoe; Smith, Kiah
ABSTRACT: Food security is influenced by various factors and policy settings. The related concept of food sovereignty, which emphasizes the rights of communities to 'define their own food systems', is also informed by political power. For Indigenous Australians, food security and food sovereignty are intimately linked with connections and access to land and water, which have been systematically disrupted under settler colonialism. Social policies continue to disrupt these connections and undermine access to food. In this paper, we explore relationships between food security, food sovereignty, and Australia's remote 'workfare' policy, the Community Development Programme (CDP), which disproportionately affects Indigenous Australians. We find that CDP undermines food security and food sovereignty by influencing the conditions for access to land, income, time and power. A lack of coordination across food and social policies creates complex, negative impacts, but sovereignty is central to improving Indigenous Australians' wellbeing and outcomes across food and work.